2019
DOI: 10.5194/tc-2019-34
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Airborne radionuclides and heavy metals in High Arctic terrestrial environment as the indicators of sources and transfers of contamination

Abstract: Abstract. A survey of airborne radioactive isotopes (137Cs, 238Pu, 239+240Pu, 241Am and 210Pb) and trace metals (Pb, Cu, Zn, Cd, Fe, Al) in tundra soils and cryoconite hole material sampled from several locations in the Kaffiøyra region revealed high spatial concentration variability of the analysed samples. Lithogenic radionuclides (230Th, 232Th, 234U, 238U) show less variability than the airborne radionuclides because their activity concentrations are controlled only by mixing of weathered material derived f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The previous investigation for the Arctic archipelago of Svalbard concluded that the terrestrial environment was primarily contaminated with bomb-derived Pu isotopes and 137 Cs, and, to a lesser extent, by 137 Cs originating from the Chernobyl accident in 1986 [15]. For initial soils and cryoconite unexplained deviations from the weapons testing were noted, but mainly for 238 Pu/ 239+240 Pu and 240 Pu/ 239 Pu activity and mass ratios, respectively [29,31,33].…”
Section: Variation Of 137 Cs/ 90 Sr and 239+240 Pu/ 90 Sr Isotopic Ramentioning
confidence: 96%
See 1 more Smart Citation
“…The previous investigation for the Arctic archipelago of Svalbard concluded that the terrestrial environment was primarily contaminated with bomb-derived Pu isotopes and 137 Cs, and, to a lesser extent, by 137 Cs originating from the Chernobyl accident in 1986 [15]. For initial soils and cryoconite unexplained deviations from the weapons testing were noted, but mainly for 238 Pu/ 239+240 Pu and 240 Pu/ 239 Pu activity and mass ratios, respectively [29,31,33].…”
Section: Variation Of 137 Cs/ 90 Sr and 239+240 Pu/ 90 Sr Isotopic Ramentioning
confidence: 96%
“…The cryoconite was collected from each sampling site, whereas the soil and peat profiles were derived only from the Werenskiold area. The details of scientific expeditions into the Werenskiold, Kafføyra and Kongsfjord areas and the description of the fieldworks were presented elsewhere [28,29,32,33,43]. Samples taken from the other study areas (i.e., Calypsobyen and Sørkapp Land), as a part of a wider scientific project, will be characterised in a future paper.…”
Section: Study Area and Samplingmentioning
confidence: 99%